THE EFFECT OF INVESTMENT DECISION, SOLVENCY, PROFITABILITY, CAPITAL STRUCTURE ON COMPANY VALUE OF MANUFACTURING INDUTRY COMPANIES IN THE CONSUMER GOODS SECTOR LISTED IN THE INDONESIA STOCK EXCHANGE IN THE PERIOD OF 2019-2022 - Ibrania Euis Anggie Sianturi; Enda Noviyanti Simorangkir; Juli Arlis Sianturi; Soni Dharma Syaputra; Putri Wahyuni (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This research aims to find out the influence of Investment Decisions, Solvency, Profitability, Structure Capital Faced by the Company Values Manufacturing Industry Consumer goods sector listed on the Stock Exchange Indonesia Securities Period 2019-2022. The research approach used in this research is research Quantitative, this type of research is descriptive and the nature of the research is casual. Method This research is a documentation method. The data analysis model used is the analysis double linear. The population of this research is the manufacturing industry companies sector 50 consumer goods registered on the Indonesian Securities Exchange for the 2019 - 2022 period company. The determination of samples using Technical purposive sampling was obtained as many as 30 companies. The value of the determination coefficient using the value of Adjusted R Square is 0.025. The results of the study show that partially, investment decisions with a value of 0.019 has no effect on the company's value, solvency with a value of - 0.351 has no effect on the company's value. Profitability with a value of 2,459 has an effect and significant on the value of the company and capital structure with a value of 1,421 has no effect on the company's value. Simultaneously with a score of 1.749 indicates that investment decisions, solvency, profitability and capital structure are not affect the value of companies in the manufacturing industry companies in the goods sector consumption listed on the Indonesia Stock Exchange for the 2019-2022 period.